Salvage Total Pelvic Exenteration with Bilateral V-Y Advancement Flap Reconstruction for Locally Recurrent Rectal Cancer - Tashiro, Jo (S. Karger AG, 2013)
Total pelvic exenteration for locally recurrent rectal cancer typically requires extensive excision of the pelvic floor with perineal skin. Due to the extensiveness of the procedure and its non-curative nature, it is controversial as purely palliative therapy. A 66-year-old male patient who had undergone abdominoperineal resection at another hospital 8 years prior was admitted to our hospital. During radiation and chemotherapy for 2 years, he complained of perineal pain, discharge, cacosmia and bleeding from a recurrent tumor. The 10 × 8 cm recurrent tumor was exposed on the perineum and the patient suffered from serious discomfort in his daily life during walking or sitting. We performed total pelvic exenteration with partial sacrectomy, after which the large perineal defect was reconstructed with a bilateral V-Y gluteus maximus advancement flap in approximately 120 min. The patient's postoperative course was satisfactory and his quality of life markedly improved.